1993
DOI: 10.1002/app.1993.070470905
|View full text |Cite
|
Sign up to set email alerts
|

On the neck‐like deformation in high‐speed spun polyamides

Abstract: SYNOPSISThe neck-like deformation process occurring in high-speed melt spinning of polyamide 66 and polyamide 6 filaments was investigated at take-up speeds of 4200 to 5500 m/min by on-line laser light scattering, thermographic contrast compensation, and wide-angle X-ray scattering ( WAXS ) measurements. New information about the onset of crystallization along the spinline was obtained by measuring simultaneously diameter and temperature profiles in the neighborhood of the neck. Crystallization rates, as a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
58
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 18 publications
14
58
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11] Many of these studies concerned PET. Our research group has studied on the fiber structure development process in the continuous laser-drawing for PET and PTT fibers through on-line WAXD and SAXS measurements [9] with synchrotron radiation systems [10,11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Many of these studies concerned PET. Our research group has studied on the fiber structure development process in the continuous laser-drawing for PET and PTT fibers through on-line WAXD and SAXS measurements [9] with synchrotron radiation systems [10,11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…Online characterization of these processes using in-laboratory X-rays has been demonstrated (Chappel, Culpin, Gosden & Tranter, 1964;Katayama, Amano & Nakamura, 1968;Spruiell & White, 1975;Haberkorn, Hahn, Breuer, Dorrer & Matthies, 1993), although low intensity seriously limits the applicability. For example, a very long exposure time is needed for good signal resolution [2-4 h for wideangle X-ray diffraction (WAXD), 12-24 h for smallangle X-ray scattering (SAXS)].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted for the on-line characterization of structure development for synthetic fibers during drawing using simultaneous synchrotron radiation as well as laboratory X-ray generators for WAXD and SAXS [10][11][12]. Schultz et al [8,9] reported that unit cell dimensions, crystallinity, and orientation were dependent on stretching temperature and strain.…”
mentioning
confidence: 99%